TMS Based TOEFL Training and Try Out (TOEFL Strategy Module) for 2019 TMT Lecturers at Ambon State Polytechnic to Get Lecturer Certification - Juvrianto Chrissunday Jakob; Ahmad Nusi; Nelda Maelissa; Hindri Febri Ana Sari; Meyke Marantika (ABDIMAS: Jurnal Pengabdian Masyarakat, 2021)
One of the requirements to pass the lecturer certification exam is to attach a TOEFL score. TOEFL itself is an abbreviation of Test of English as a Foreign Language which is used to measure how far a person's English ability is. In the various findings and field observations made, almost all lecturers who will carry out the 2019 TMT lecturer certification at the Ambon State Polytechnic have the same difficulties when they want to face the TOEFL test. Therefore, the Ambon State Polytechnic Community Service Team took the initiative to conduct TOEFL training activities for TMT 2019 lecturers so that they could overcome their difficulties on the TOEFL test by using modules compiled by the team. The results of this service activity show that the English language skills possessed by the lecturers have increased after the training. This can be seen from their pre-test and post-test scores. It is hoped that after going through this activity, they can test their abilities by carrying out the TOEFL test and can penetrate lecturer certification.